Potensi Likuifaksi Tanah Pasir Di Atas Tanah Lunak Dengan Variasi Tebal Timbunan Pasir Melalui Uji Model Laboratorium - Bahrul Junaidi; Agus Ika Putra; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Buildings in Riau, especially Pekanbaru City, are generally established on peatlands covered in sand embankment. Earthquakes often occur in the western region of the island of Sumatra due to its position along with two tectonic plate collision of earth, Indian and Eurasian plate. One of earthquake activity aftermath is liquefaction. Liquefaction can be defined as the loss of shear strength of soil due to an increase in excess pore water pressure caused by cyclical load, therefore the total stress of ground is almost entirely replaced by pore water pressure. The aim of this research is to know the influence of embankment thickness and acceleration of vibration against pore water pressure increment and soil settlement. This research was conducted by laboratory model test using shaking table. The acceleration variation used were 0.25 g and 0.32 g. The thickness variation of sand embankment used were 10 cm, 15 cm, and 20 cm placed on a 10 cm peat soil layer and given a load 40 kg/m2. Water level elevation as high as the sand layer each variation. The results of this research show that with the addition of the sand embankment thickness takes longer time to reach maximum pore water pressure increment. The thicker of sand embankment take longer time to reach maximum soil settlement during liquefaction. The addition of acceleration values leads to larger increment of pore water pressure and soil settlement, but the time it takes for pore water pressure begin to stabilize tends to be faster.Keyword : Liquefaction, embankment, peat soil, excess pore water pressure, shaking table